2020
DOI: 10.1016/j.chembiol.2020.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Triplexed Affinity Reagents to Sample the Mammalian Inositol Pyrophosphate Interactome

Abstract: Highlights d Analogs of Inositol pyrophosphate messengers were derivatized at different positions d Multiplexed affinity matrices were generated and validated d 300-400 putative interacting proteins were identified from mammalian lysates d Label-free quantification uncovered binding preferences of closely related messengers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 74 publications
4
36
0
Order By: Relevance
“…Analysis of cell lysates from Saccharomyces cerevisiae, Trypanosoma cruzi, and human cell lines uncovered several protein domains that appear to exhibit high affinity for InsPs and PP-InsPs, including FERM, 14-3-3, and RasGAP domains. 24,30,31 These current system-wide data sets, in combination with accessible chemical and enzymatic syntheses of PP-InsPs, 32−38 provide a vantage point for the quantitative biochemical validation and characterization of PP-InsP− protein interactions. In principle, there are a variety of biochemical methods for investigating the interaction of PP-InsPs with putative receptors and binding proteins (Figure 1B).…”
mentioning
confidence: 99%
“…Analysis of cell lysates from Saccharomyces cerevisiae, Trypanosoma cruzi, and human cell lines uncovered several protein domains that appear to exhibit high affinity for InsPs and PP-InsPs, including FERM, 14-3-3, and RasGAP domains. 24,30,31 These current system-wide data sets, in combination with accessible chemical and enzymatic syntheses of PP-InsPs, 32−38 provide a vantage point for the quantitative biochemical validation and characterization of PP-InsP− protein interactions. In principle, there are a variety of biochemical methods for investigating the interaction of PP-InsPs with putative receptors and binding proteins (Figure 1B).…”
mentioning
confidence: 99%
“…Another mode of PP-InsP signal transduction is associated with their similarity to membrane bound PIPs. Many PP-InsP binding proteins contain PIP binding domains, such as PH and C2 domains (Luo et al, 2003;Chakraborty et al, 2010;Gokhale et al, 2013;Furkert et al, 2020). Recent studies have shown that PP-InsPs can effectively compete with PIPs and can delocalize proteins from the membrane, thereby regulating membrane-cytosol communication (Gokhale et al, 2013;Lorenzo-Orts et al, 2020;Pavlovic et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…To investigate this scenario, identifying the interacting components of other SPX proteins becomes a prerequisite. Nevertheless, it is possible that the binding of PP-InsP to the SPX domain per se may regulate the function of the protein it bears independent of interacting partners as a result of structural changes ( Furkert et al, 2020 ; Lorenzo‐Orts et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…By using synthetic InsP 7 as bait to search for its interacting proteins, a recent study identified a myriad of proteins absent of SPX domains, among which are the ribose-phosphate pyrophosphokinases 1 and 2 (PRPS1 and PRPS2) and their associated proteins PRPSAP1 and PRPSAP2 that are involved in nucleotide biosynthesis ( Furkert et al, 2020 ). This finding suggests a potential correlation between the Pi-signaling and nucleotide biosynthesis and inspires speculation about whether SPX-independent proteins can perceive PP-InsPs to modulate cellular Pi homeostasis.…”
Section: Introductionmentioning
confidence: 99%